2020
DOI: 10.1038/s41467-020-17916-9
|View full text |Cite
|
Sign up to set email alerts
|

Widespread protein lysine acetylation in gut microbiome and its alterations in patients with Crohn’s disease

Abstract: Lysine acetylation (Kac), an abundant post-translational modification (PTM) in prokaryotes, regulates various microbial metabolic pathways. However, no studies have examined protein Kac at the microbiome level, and it remains unknown whether Kac level is altered in patient microbiomes. Herein, we use a peptide immuno-affinity enrichment strategy coupled with mass spectrometry to characterize protein Kac in the microbiome, which successfully identifies 35,200 Kac peptides from microbial or human proteins in gut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 64 publications
0
53
0
Order By: Relevance
“…Lysine acetylation might be an important factor that affects obesity by regulating energy homeostasis [55]. Zhang et al [56] reported that most acetylphosphate-generating enzymes are derived from Firmicutes that have higher lysine acetylome-to-metaproteome ratios than other bacterial phyla. Threonine levels were higher in the serum from the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Lysine acetylation might be an important factor that affects obesity by regulating energy homeostasis [55]. Zhang et al [56] reported that most acetylphosphate-generating enzymes are derived from Firmicutes that have higher lysine acetylome-to-metaproteome ratios than other bacterial phyla. Threonine levels were higher in the serum from the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The study of PTMs using proteomics typically requires an enrichment or depletion step, and a limited number of studies have profiled PTMs in the human gut environment from intestinal biopsies or stool samples. For example, a pioneering study has used a peptide immuno-affinity enrichment strategy to profile an abundant PTM in prokaryotes, lysine acetylation, in the gut microbiome [92] . The study identified lysine-acetylated sites on both host and microbial proteins that were differentially abundant in patients with Crohn's disease and healthy controls.…”
Section: Current Challenges Of Stool-based Metaproteomicsmentioning
confidence: 99%
“…This microbiomewide acetylome approach claried that aberrant Kac protein changes in the microbiome might be related to CD development. 21 By using titanium dioxide (TiO 2 ) for the efficient enrichment of phosphopeptides, He et al used MS to analyze and quantitate the phosphoproteomic changes in a HBx-transgenic mouse model of hepatocellular carcinoma (HCC), leading to the proling of 22 539 phosphorylation sites in 5431 proteins, and revealing elevated kinase activities of Src family kinases (SFKs), protein kinase C (PKCs), mitogen-activated protein kinases (MAPKs), and Rho-associated kinases (e.g., ROCK2) in HCC. 22 By identifying the main kinases in various tumor tissues and the corresponding para-tissues, kinase activity can be targeted and extended to personalized medicine, and appropriate drug combinations can be used to benet individual patients.…”
Section: Comprehensive Biochemical Proling -"What"mentioning
confidence: 99%